Nanosphere Lithography for Structuring Polycrystalline Diamond Films - Mária Domonkos; Pavel Demo; Alexander Kromka (Crystals, 2020)
This paper deals with the structuring of polycrystalline diamond thin films using the technique of nanosphere lithography. The presented multistep approaches relied on a spin-coated self-assembled monolayer of polystyrene spheres, which served as a lithographic mask for the further custom nanofabrication steps. Various arrays of diamond nanostructures—close-packed and non-close-packed monolayers over substrates with various levels of surface roughness, noble metal films over nanosphere arrays, ordered arrays of holes, and unordered pores—were created using reactive ion etching, chemical vapour deposition, metallization, and/or lift-off processes. The size and shape of the lithographic mask was altered using oxygen plasma etching. The periodicity of the final structure was defined by the initial diameter of the spheres. The surface morphology of the samples was characterized using scanning electron microscopy. The advantages and limitations of the fabrication technique are discussed. Finally, the potential applications (e.g., photonics, plasmonics) of the obtained nanostructures are reviewed.